Peningkatan Perilaku Hidup Bersih dan Sehat (PHBS) melalui Edukasi dan Demonstrasi Cuci Tangan di Sekolah Dasar - Musdalifah Musdalifah; Idris Idris; Lorensius Lonik; Rezki Auliah; Yudi Muammar; Rahmat Pannyiwi; Andi Nursiah (Sahabat Sosial: Jurnal Pengabdian Masyarakat, 2025)
Clean and Healthy Living Behavior (PHBS) in elementary school children is an important factor in preventing infectious diseases, such as diarrhea and respiratory infections. However, many students still do not practice handwashing correctly and regularly. This community service program aims to improve PHBS behavior through education and demonstrations of handwashing with soap in elementary schools. Activities included interactive counseling, six-step handwashing demonstrations, hands-on practice by students, and knowledge and skills assessments. The results showed a significant increase in students' knowledge of PHBS and their ability to practice proper handwashing. This program is expected to reduce the risk of infectious diseases and foster sustainable hygiene habits in schools.